2017
DOI: 10.1136/bmjopen-2016-011916
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis in early and chronic rheumatoid arthritis: a prospective follow-up study in Finnish population

Abstract: ObjectivesTo investigate the association between rheumatoid arthritis (RA) and periodontitis with special emphasis on the role of antirheumatic drugs in periodontal health.DesignProspective follow-up study. Patients with early untreated RA and chronic active RA were examined at baseline and 16 months later. Controls were examined once.Settings and participantsThe study was conducted in Finland from September 2005 to May 2014 at the Helsinki University Hospital. Overall, 124 participants were recruited for dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
88
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 54 publications
(46 reference statements)
8
88
0
Order By: Relevance
“…However, few studies have reported periodontitis to be a potential source of infection in PLA and no studies have confirmed the relationship between periodontitis and PLA . Our results indicated that exposure to periodontitis increased the risk of PLA (aOR = 2.31, 95% CI = 1.37‐3.90, P = .0018) in those aged 20‐49 years, which is similar to the results reported by Chen et al, who found that periodontitis could increase the risk of atrial fibrillation or flutter in patients, and those of Ayravainen et al, who confirmed that periodontitis increased the risk of rheumatoid arthritis.…”
Section: Discussionsupporting
confidence: 86%
“…However, few studies have reported periodontitis to be a potential source of infection in PLA and no studies have confirmed the relationship between periodontitis and PLA . Our results indicated that exposure to periodontitis increased the risk of PLA (aOR = 2.31, 95% CI = 1.37‐3.90, P = .0018) in those aged 20‐49 years, which is similar to the results reported by Chen et al, who found that periodontitis could increase the risk of atrial fibrillation or flutter in patients, and those of Ayravainen et al, who confirmed that periodontitis increased the risk of rheumatoid arthritis.…”
Section: Discussionsupporting
confidence: 86%
“…Both involve gene‐environment interaction, aberrant immune activation, and long‐standing chronic inflammation. A positive association of RA and PD is reported by a few epidemiologic studies . Shared risk factors such as smoking, older age, and HLA‐DRB1 genotype may explain this association in part.…”
Section: Introductionmentioning
confidence: 95%
“…Various relationships have been reported between periodontitis and systemic diseases such as diabetes, cardiovascular disease, and stroke . Recent studies have suggested a bidirectional relationship between periodontal disease and rheumatoid arthritis (RA) …”
mentioning
confidence: 99%
“…Therefore, the ability of RA patients to perform oral hygiene should be considered when investigating the pathogenic relationship between RA and periodontitis. A few case‐control studies have shown a significant association between RA and periodontitis after considering plaque control status, but others did not consider oral hygiene status as a factor . Another case‐control study initially found a significant association between juvenile idiopathic arthritis (JIA) and periodontal disease, but it disappeared after adjusting for the plaque index .…”
mentioning
confidence: 99%
See 1 more Smart Citation